QUIZIZZ-ASSISTED SERIOUSLY PERUSING IN ELT CLASSROOM: EFL AUXILLARY UNDERSTUDIES ENCOUNTRES - Ayunda Shintya; Iwan Ridwan (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
This research reports the findings of action research on Students’ Experience using Quizizz-Assisted on Intensive Reading in ELT Classsroom. The aim of this research is to capture students’ experience towards using Quizizz-Assisted on intensive reading in ELT classroom. This research was conducted at one of junior high school in Cikarang in the academic year 2020/2021. The participants of this research were five students and an English teacher. This research used qualitative. The data collection obtained through observation and interview. This research found that Quizizz helps students motivation in learning Reading in ELT classroom. And also helped the students to build fun teaching reading, make the students interest to gain more experience to teaching intensive reading in classroom. The abstract should be clearly written and readily comprehensible to the broad readership. It should provide a concise summary of the objectives, methodology (including the species studied), key results, and major conclusions of the study. It should be written in complete sentences, without subheadings. And it provides two languages (Bahasa Indonesia and English). Line and paragraph spacing is 1.0 with font size 11. Write abstract by using times new roman and italiced your text.  Keywords: Students experience, Quizizz, Intensive Reading, ELT